Establishing trust through quality content: A preliminary study of Malaysia e-commerce blogs - Hassan, Syahida; Zambri, Suzana; Kasiran, Mohd Khairudin; Mahli, Mohamad Tarmidi; Abd Ghani, Nor Farzana; Muhammad, Muziah (2011)
Since 2007, the use of blog as an e-commerce site has become popular in Malaysia. As more people are connected to the Internet through faster connection, significant changes can be seen in e-commerce usage. Nonetheless trust remains a major issue in this model. One of the web trust process is trust in the information displayed on the e-commerce site. Information displayed on the blog is believed to be one of the important factors to gain the consumer trust. This paper is a preliminary study particularly focusing on the use of information to establish trust in Malaysia ecommerce blogs. Samples of 100 Malaysia e-commerce blogs were studied to identify the information that is shared by the owner of respective e-commerce blogs.Descriptive statistic will be used to discuss the finding. Findings from this paper can be used as a guideline for entrepreneurs whom intend to use blogs for e-commerce purposes.